2020
DOI: 10.1088/1755-1315/499/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical characteristics in peat lands of Aceh Jaya District, Indonesia

Abstract: This study aims to determine the physical and chemical characteristics of the peat lands (Histosols) in Aceh Jaya District using descriptive method. The results showed that some physical characteristics such as: water saturation in drilling-M1 (fibric soil materials) was 786.06% higher than drilling-M2 (hemic soil materials) and drilling-M3 (sapric soil materials) were 568.01% and 549.97%, respectively. Bulk density (BD) of drilling-M1, drilling-M2 and drilling-M3 are very low (0.08 - 0.12 g cm−3). Porosity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…Exchangeable K in fibric peat (0.3 cmol(+)/kg) was low, and it was significantly different from very high K status in hemic (1.1 cmol(+)/kg) and moderate status in sapric (0.5 cmol(+)/kg). Higher K status in hemic and sapric peat compared to fibric peat was also reported by Arabia et al [11], as well as exchangeable Ca in fibric peat (9.1 cmol(+)/kg), while in hemic (6.1 cmol(+)/kg) were moderate status, was higher than sapric peat (1.0 cmol(+)/kg) (Table 1), It was also in line with the report of Arabia et al [11]. The concentration of exchangeable Mg was high in all types of peat, which was in line with the Arabia et al report [11], which also predominantly found very high-status Mg in fibric, hemic and sapric peat.…”
Section: The Nutrient Status In Each Peat Before Treatedsupporting
confidence: 79%
See 1 more Smart Citation
“…Exchangeable K in fibric peat (0.3 cmol(+)/kg) was low, and it was significantly different from very high K status in hemic (1.1 cmol(+)/kg) and moderate status in sapric (0.5 cmol(+)/kg). Higher K status in hemic and sapric peat compared to fibric peat was also reported by Arabia et al [11], as well as exchangeable Ca in fibric peat (9.1 cmol(+)/kg), while in hemic (6.1 cmol(+)/kg) were moderate status, was higher than sapric peat (1.0 cmol(+)/kg) (Table 1), It was also in line with the report of Arabia et al [11]. The concentration of exchangeable Mg was high in all types of peat, which was in line with the Arabia et al report [11], which also predominantly found very high-status Mg in fibric, hemic and sapric peat.…”
Section: The Nutrient Status In Each Peat Before Treatedsupporting
confidence: 79%
“…Higher K status in hemic and sapric peat compared to fibric peat was also reported by Arabia et al [11], as well as exchangeable Ca in fibric peat (9.1 cmol(+)/kg), while in hemic (6.1 cmol(+)/kg) were moderate status, was higher than sapric peat (1.0 cmol(+)/kg) (Table 1), It was also in line with the report of Arabia et al [11]. The concentration of exchangeable Mg was high in all types of peat, which was in line with the Arabia et al report [11], which also predominantly found very high-status Mg in fibric, hemic and sapric peat. Numbers in the same row followed by different letters were significantly different at the significance level of 0.05.…”
Section: The Nutrient Status In Each Peat Before Treatedsupporting
confidence: 79%
“…Peat has good adsorption properties and is often used as an effective filter material for suspended and dissolved solid particles. Decomposed peat has a relatively high porosity of about 95% [34]. -Wood chips (20-50 mm) and sawdust (0.1-2 mm) are wood by-products, waste materials and low-cost sorbents applied mainly to the removal of organic compounds from wastewater [35,36].…”
Section: Methodsmentioning
confidence: 99%
“…The ash content decreases with the depth of the peat. Oligotrophic peat generally consists of thick peat and poor nutrients (Arabia et al, 2020).…”
Section: Content Of Ash and Organic C In Peat Soilmentioning
confidence: 99%
“…Based on bulk density value, the peat in the three cropping uses is classified as fibrous peat, especially in layers > 50 cm. According to Arabia et al (2020), fibrous peat has a bulk density (BV) < 0.075 g cm -3 and total porosity > 90%, hemic if BV is 0.075-0.195 g cm -3 and total porosity is 85%-90%, and sapric if BV > 0.195 g cm -3 and total porosity < 85%.…”
Section: Content Of Ash and Organic C In Peat Soilmentioning
confidence: 99%